The devil's element : phosphorus and a world out of balance - Egan, Dan (W.W. Norton & Company, 2023)
"The story of phosphorus spans the globe and vast tracts of human history. The race to mine phosphorus took people from the battlefields of Waterloo, which were looted for the bones of fallen soldiers, to the fabled guano islands off Peru, the Bone Valley of Florida, and the sand dunes of the Western Sahara. Over the past century, phosphorus has made farming vastly more productive, feeding the enormous increase in the human population. Yet, as Egan harrowingly reports, our overreliance on this vital crop nutrient is today causing toxic algae blooms and "dead zones" in waterways from the coasts of Florida to the Mississippi River basin to the Great Lakes and beyond. Egan also explores the alarming reality that diminishing access to phosphorus poses a threat to the food system worldwide--which risks rising conflict and even war"--